The global, regional, and national burden of stomach cancer among adolescents and young adults in 204 countries and territories, 1990–2019: A population-based study - Zhang, Ziqiang; Wang, Jun; Song, Ning; Shi, Liubin; Du, Jianjun (Frontiers in Public Health, 2023)
Background: Stomach cancer is a significant health problem in many countries. But healthcare needs of adolescents and young adults (AYAs) stomach cancer patients have been historically neglected. An accurate appraisal of the burden of AYA stomach cancer is crucial to formulating effective preventive strategies. In this study, we report the most recent estimates of AYA stomach cancer burden concerning socio-demographic index (SDI) in 204 countries and territories between 1990 and 2019. Methods: Estimates from the Global Burden of Disease study 2019 were used to analyze incidence, mortality, and disability-adjusted life years (DALYs) due to AYA stomach cancer at global, regional, and national levels. Association between AYA stomach cancer burden and SDI were investigated. All estimates are reported as absolute numbers and age-standardized rates, which were standardized to the GBD world population and reported per 100,000 population. Results: In 2019, there were 49,000 incident cases, 27,895 deaths, and 1.57 million DALYs due to AYA stomach cancer globally. The highest age-standardized incidence rate occurred in East Asia (2.42 [women] and 4.71 [men] per 100,000 person-years) and high-income Asia Pacific (3.16 [women] and 2.61 [men] per 100,000 person-years). Age-standardized death (1.53 [women] and 2.65 [men] per 100,000 person-years) and DALY (150.96 [women] and 87.13 [men] per 100,000 person-years) rates were highest in Oceania. Compared with 1990, in 2019 more than 1,075 more incident cases of AYA stomach cancer were estimated with a decrease of 7,784 deaths. Despite the increase in absolute number of incident cases, the worldwide age-standardized rates of AYA stomach cancer (incidence, deaths, and DALYs) have declined since 1990. The drop in the disease burden was associated with an improved SDI. Globally, 24.41% of the age-standardized DALYs were attributable to a high-sodium diet in both sexes combined, and 0.57% of the age-standardized DALYs were attributable to smoking in men. Conclusion: The global burden of AYA stomach cancer is substantial, especially in developing regions. Capacity-building activities for AYA stomach cancer will benefit the younger generation and population health worldwide.